Effectiveness of Telerehabilitation on Hamstring Flexibility in Healthy Adults - Genç, Hazal; Poyraz İşleyen, Tuğçe; Tahmaz, Tuğçe; Aydoğan, Yeldağ; Atilgan, Esra (Physical Education Theory and Methodology, 2022)
Background. Telerehabilitation used as an exercise method has become increasingly common in recent years. Various methods have been used to increase hamstring flexibility, but more research is required on the optimal program. The study purpose was to investigate the effect of hamstring stretching exercises given as telerehabilitation and home exercise program on hamstring flexibility. Materials and methods. Sixty-eight healthy adults were randomly assigned to two groups, namely telerehabilitation and home exercise. Exercises were performed for 8 weeks (4 sessions/week) in both groups. Active and passive range of motion (ROM), sit and reach test (SRT), and International Physical Activity Questionnaire Short Form (IPAQ-SF) were conducted in the pre- and post-intervention and after a 6-month period. Results. At the end of 8 weeks, a significant improvement was observed in the SRT scores in both the telerehabilitation group (p = 0.001) and the home exercise group (p = 0.001). In addition, significant improvements were observed in the passive ROM measurements of both the telerehabilitation group (p = 0.005) and the home exercise group (p = 0.001). At the end of 8 weeks, the telerehabilitation group was found to be significantly superior to the home exercise group in the SRT results (p = 0.034). As for the long-term results, significant improvement was maintained in both SRT (p = 0.001) and passive ROM (p = 0.014) in the telerehabilitation group. Conclusions. Eight-week telerehabilitation and home exercise program was observed to have positive effects on passive and active ROM. The telerehabilitation method may prove to be more effective than the home exercise method in the long term.